2020
DOI: 10.3892/etm.2020.8786
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the health effects on workers exposed to respirable crystalline silica during outdoor and underground construction projects

Abstract: Chronic exposure of workers to powder containing crystalline silica (Silicon dioxide; SiO 2) can lead to chronic lung diseases (lung cancer, silicosis, etc.). Aim of this study was to evaluate the exposure of Greek construction workers to SiO 2 and describe their pulmonary function. The study involved 86 outdoor and underground workers. Medical and professional history was obtained, and breath samples were collected at morning hours through a mask for the determination of SiO 2 levels. Pulmonary function tests… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Due to the presence of quartz in dust, the inhalation of the quartz particles in the size of 0.5-0.7 µm may produce diseases such as chronic silicosis, acute silicosis, accelerated 15 silicosis, and silica tuberculosis (Keramydas et al 2020, Ross et al 1993. Presence of quartz in the air might be a carcinogenic agent (Downward et al 2017, Keramydas et al 2020. The inhalation of hematite along with other substances in the dust might create lung disease.…”
Section: Influence Of Dust Dispersed In Water On Optical Properties Of Glass and Human Beingmentioning
confidence: 99%
“…Due to the presence of quartz in dust, the inhalation of the quartz particles in the size of 0.5-0.7 µm may produce diseases such as chronic silicosis, acute silicosis, accelerated 15 silicosis, and silica tuberculosis (Keramydas et al 2020, Ross et al 1993. Presence of quartz in the air might be a carcinogenic agent (Downward et al 2017, Keramydas et al 2020. The inhalation of hematite along with other substances in the dust might create lung disease.…”
Section: Influence Of Dust Dispersed In Water On Optical Properties Of Glass and Human Beingmentioning
confidence: 99%
“…In the same study, it was found that noise exposures to underground workers were independent of age which is similar to results obtained from this present study. In addition, Keramydas 26 reported in a similar study that the number of mine workers with hearing impairment increased exponentially with age until age 50, at which point 90% of miners had a hearing impairment, significantly associated with noise exposures above the PEL.…”
Section: Discussionmentioning
confidence: 85%
“…In a study carried out by Keramydas et al 14 , noted 11% of construction workers to have abnormal FEF 25%-75% . However, in this study, all industries (except Dharma Arts) showed prevalence of abnormal FEF 25%-75% above 20%.…”
Section: Pulmonary Function Test Findingsmentioning
confidence: 97%